Muslim Fashion Style, Personal Branding, Trust and Purchase Decisions Through Social Media: Gaya Busana Muslim, Personal Branding, Kepercayaan dan Keputusan Pembelian Melalui Media Sosial - Kamuri, Klaasvakumok Jehezkielomi; Manongga, Irience Rachel Agatha; Anabuni, Andrias Umbu Tuku; Riwu, Yonas Ferdinand (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2024)
This study examines the role of Muslim fashion as a form of personal branding in online shopping through social media, particularly platforms like TikTok. While previous research has explored lifestyle and personality as aspects of personal branding, this study focuses specifically on Muslim fashion and its impact on consumer trust and purchasing decisions. Using a quantitative explanatory research approach, data were analyzed with the Smart Partial Least Squares (Smart PLS) application. The results reveal that Muslim fashion significantly influences sellers' personal branding, with a strong personal brand enhancing consumer trust in the seller. The findings suggest that sellers who align their Muslim fashion with consumer perceptions can build stronger trust, broaden their customer base, attract new buyers, and ultimately increase sales. These insights offer valuable guidance for sellers aiming to improve their marketing strategies through consistent, transparent content and services on social media.